2008
DOI: 10.13057/biodiv/d100206
|View full text |Cite
|
Sign up to set email alerts
|

Reef Fish Status in Northern Acehnese Reef Based on Management Type

Abstract: The objectives of this study were to provide reliable data and information on reef fish in the northern Aceh region of Wehand Aceh islands based on management types. This research use underwater visual census techniques at 29 sites aroundWeh Island and Aceh Islands. Reef fish abundance in area that were protected under the management of Panglima Laot ofSabang Weh Island (32505 no.ha-1) and biomass (748 kg.ha-1) were also significantly higher than in Aceh Islands which is open access areas (abundance=9539 no.ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 12 publications
0
15
0
4
Order By: Relevance
“…Aceh Province, Indonesia has an abundance of fishery resources with at least 114 species of freshwater and brackish-water fishes recorded in this region (Muchlisin and Siti-Azizah 2009). In addition, Muchlisin et al (2015a) report that 73 species freshwater and brackish-water fishes inhabit the Tripa peat swamp forest, while Rudi et al (2009) and Rudi and Muchsin (2011) report that at least 97 species of coral reef fishes occur in Aceh waters. Furthermore, Muchlisin (2013) reports that 14 freshwater species of high economic fish value are found in Aceh waters, including Tor tambra (Val.…”
Section: Introductionmentioning
confidence: 99%
“…Aceh Province, Indonesia has an abundance of fishery resources with at least 114 species of freshwater and brackish-water fishes recorded in this region (Muchlisin and Siti-Azizah 2009). In addition, Muchlisin et al (2015a) report that 73 species freshwater and brackish-water fishes inhabit the Tripa peat swamp forest, while Rudi et al (2009) and Rudi and Muchsin (2011) report that at least 97 species of coral reef fishes occur in Aceh waters. Furthermore, Muchlisin (2013) reports that 14 freshwater species of high economic fish value are found in Aceh waters, including Tor tambra (Val.…”
Section: Introductionmentioning
confidence: 99%
“…Rudi et al (2009) has shown that coral cover has strong correlation with abundance and diversity of reef fishes in this area. In the higher coral cover, the fish abundance and diversity were also higher.…”
Section: Discussionmentioning
confidence: 92%
“…Fauna and flora of the island consist of species from Indian Ocean and from eastern Indonesia. In general, coral reef condition of Weh Island was better compare with Aceh Island in term of hard coral cover because of different type of management in past time (Baird et al 2005;Campbell et al 2007;Rudi et al 2009). It is also known that Weh Island is the most popular destination for marine tourism.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a study regarding coral reefs and coral reef fishes in Simeulue Island is just preliminary. The previous reports were mostly focused on northern region of Aceh (Rudi et al, 2009;Ulfah, 2011;Baird et al, 2012;Fadli et al, 2014;Aldyza et al, 2015). According to the local fishermen in Simeulue, the most serious threats to the coral reefs in Ganting, Simueluecut, and Labuhan Bajau are marine pollution, fishing boats activities, and marine ecotourism.…”
Section: Introductionmentioning
confidence: 99%